2000
DOI: 10.1007/s102010070029
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of fluctuations in salinity and water quality in brackish Lake Obuchi

Abstract: Fluctuations in the salinity and physicochemical characteristics of water quality were surveyed in brackish Lake Obuchi on the Shimokita Peninsula in Aomori, Japan. The mean salinity in the surface layer in all regions of Lake Obuchi was about 10 psu, whereas in the basin region at depths of greater than 3 m it was 20 psu. Furthermore, all the year round the halocline was formed at depths of 1-4 m. The maximum density gradient along a vertical axis in the center of the lake was observed at depths of 1-2 m in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…1) in the center of the lake, where it attains its maximum depth, we confirmed that a strong salinity gradient (halocline) was formed between the upper and lower layers (Ueda et al 2000). The periodic fluctuations in salinity at this sampling station did not correspond to the meteorological tide (Ueda et al 2002), indicating that the water at this station was not immediately affected by the tide.…”
Section: Field Surveysupporting
confidence: 82%
“…1) in the center of the lake, where it attains its maximum depth, we confirmed that a strong salinity gradient (halocline) was formed between the upper and lower layers (Ueda et al 2000). The periodic fluctuations in salinity at this sampling station did not correspond to the meteorological tide (Ueda et al 2002), indicating that the water at this station was not immediately affected by the tide.…”
Section: Field Surveysupporting
confidence: 82%
“…They argue that this concentration is maintained due to the increase of As (V) in the accumulated arsenic compounds in the sediments. The commensurate increase in As, Fe and Mn suggests that the reducing condition exists in the bottom water layers during summer stratification as indicated by August dissolved oxygen profiles (Sohrin et al 1997;Ueda et al 2000).…”
Section: Seasonal Variations In the Water Columnmentioning
confidence: 97%
“…Payne and Waite (1991) proposed that uranium was scavenged by iron(III) hydroxide or manganese(IV) oxide and settled on the bottom. The concentrations of iron and manganese in the wa- ters of Lake Obuchi are usually high in the bottom layer during the summer (Ueda et al 2000). Therefore, it can be presumed that uranium in the bottom water may be precipitated with iron(III) hydroxide or manganese(IV) oxide formed by oxidation with dissolved oxygen.…”
Section: Concentration Of 238 U In Extracted Fractionmentioning
confidence: 98%
“…The water qualities of coastal lagoons and brackish lakes are influenced by interactions between marine and terrestrial factors, reflecting their hydrochemical complex and ecologically unique nature (Ohtake et al 1982). Lake Obuchi has a crescentshaped tray, and the bottom layer is in a reduced state in the summer because of the halocline (Ueda et al 2000). Therefore, we presume that uranium in the lake water in the bottom layer may be precipitated by reduction to insoluble U(IV).…”
Section: Introductionmentioning
confidence: 97%